1987
DOI: 10.2113/gsecongeo.82.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and geochemical studies of the Emperor gold telluride deposit, Fiji

Abstract: The Emperor gold telluride deposit consists of a system of quartz-filled fractures lying on the margin of a caldera in the Mba Volcanics, of Miocene age, in the north of Viti Levu, Fiji. The veins filled fractures that developed mainly in precaldera basalts. The veins are both preand postfaulting, contain vugs, and show evidence of repeated opening. They are dominantly quartz with minor pyrite, tellurides, gold, sphalerite, arsenopyrite, chalcopyrite, tetrahedrite, galena, dolomite, calcite, and mica (part V r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
9

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 10 publications
4
65
0
9
Order By: Relevance
“…(Kelly and Goddard, 1969;Saunders and May, 1986;Ahmad et al, 1987). Textural evidence shows that tellurium mineral was formed after sulfide mineral and this concludes that magmatic sulfur was put to the fluid first then followed by input of tellurium.…”
Section: Discussionmentioning
confidence: 98%
“…(Kelly and Goddard, 1969;Saunders and May, 1986;Ahmad et al, 1987). Textural evidence shows that tellurium mineral was formed after sulfide mineral and this concludes that magmatic sulfur was put to the fluid first then followed by input of tellurium.…”
Section: Discussionmentioning
confidence: 98%
“…7 Hydrogen versus oxygen isotope diagram and histogram, displaying stable isotope systematics of hydrothermal fluids from Apigania Bay mineralization. The "Meteoric water line" and the "Subductionrelated vapor, arc and crystal felsic magma" (Hedenquist and Lowenstern 1994) are also displayed ficients of dissolved species were derived from Helgeson and Kirkham (1974a, b), Harvie et al (1984), Henley et al (1984), Ahmad et al (1987) and Zhang and Spry (1994). From the reaction (1) log a SiO 2 aq ð Þ values of −1.9, −2.5 and −2.8 were derived at 200°C, 175°C, and 150°C, respectively:…”
Section: Physicochemical Conditions Of Metallic Mineral Formationmentioning
confidence: 99%
“…Experimental studies have showed that magnesium has the capacity to increase the rate of hydrogen dissociation, slow down its adsorption kinetics, and lead hydrogen-bearing gases to condense (Swartz et al 1999). This hypothesis is supported by the presence of magnesium minerals in the most studied Ag-Au-Te ore deposits such as: dolomite-talc-brucite (Panormos Bay; Tombros et al 2004Tombros et al , 2005Tombros et al , 2007, Mg-chlorite (Acupan; Cooke et al 1996;Cooke and McPhail (2001), dolomite (Cripple Creek; Thompson et al 1985;Kelley et al 1998), dolomite and Mg-chlorite (Emperor, Tuvatu; Ahmad et al 1987;Scherbarth and Spry 2006), roscoelite and dolomite (Porgera; Richards and Kerrich 1993;Ronacher et al 2004) and Mg-chlorite and manganese ores (Sunnyside mine; Casadevall and Ohmoto 1977).…”
mentioning
confidence: 92%
“…Από την ισορροπία H 2 S<->2H + +S _ , (Casadevall & Omhotto, 1977, Henley et al, 1984 (Barnes, 1979). Τέλος από την ισορροπία H 2 Te«H + +HTe", (Ahmad et al, 1987), για logK= -5,5, pH=5,6, T=250°C και [H 2 Te] = 10" 6 · 5 , (Ahmad et al, 1987, Me PHail, 1995 για το ρευστό που αποθέτει τα τελλουρίδια, υπολογίζουμε [HTe]=10 39 . Η συγκέντρωση των ιόντων κυμαίνεται στην τιμή logLHTe"= -3,9 και η m LHTe " =9,78 ppb, (Πίνακες 2, 3).…”
Section: πίνακας 1 τιμές σταθερών γινομένου διαλυτότητας (Logkunclassified
“…Από την ισορροπία για τον αρσενοπυρίτη σε ιστολογική ισορροπία με σιδηροπυρίτη, FeAsS+S"V»FeS 2 +2As~, (Cooke et al, 1996) (Ahmad et al, 1987, Cooke et al, 1996, για logK=-8,2, pH=5,6, T=250°C, loga , δηλαδή ^Σ^+=-4,855 και m + =1,51 ppb. Από την ισορροπία για τον καλαβερίτη, Au+Te 2 <-»AuTe 2 , (Ahmad et al, 1987, Cooke et al, 1996, για logK=-9,38, pH=5,6, T=250°C, loga Te2 =-6,7 και [AuTeJ = l, υπολογίζουμε [Au] Στάδιο VII.…”
Section: πίνακας 1 τιμές σταθερών γινομένου διαλυτότητας (Logkunclassified